Dividend Policy Determinants and Stock Price Volatility in Selected African Stock Markets - Ajao, Mayowa Gabriel; Robinson, Fredrick Edosa (International Journal of Finance Research, 2022)
The study examined the impact of dividend policy determinants on stock price volatility in Sub Sahara Africa. Three (3) economies (Nigeria, Kenya and South Africa) were selected from among the 51 economies in the region, and data spanning 9 years (2011-2019) were obtained and subjected to econometric analyses. The Generalized Autoregressive Conditional Heteroskedacity (GARCH) was used to ascertain and generate the volatility properties of the stock prices, while the panel Autoregressive Distributed Lag (ARDL) technique was used to capture the relationship between dividend policy determinants and stock price volatility. The independent variables analyzed in this study are leverage (LEV), firm size (FSIZE), dividend yield (DY), earnings per share (EPS) and dividend payout (DPO) while the dependent variable was the volatility in stock price (SPV). Findings show that all of the variables considered have varying degree of relationships with stock price volatility both in the long run and short run in the three countries. The pooled result indicated that DPO, LEV, FSIZE, DY and EPS had a significant relationship with stock price volatility within the study period in the long run but no short run relationship could be confirmed for the combined samples. The study concluded that dividend payout, dividend yield and earnings per share are significant factors that can be used for predicting the volatile movement in stock price in the African stock markets. The study recommended that dividend payment should be consistent and smoothed to disrupt volatility of stock prices since dividend payment is found to be significant determinant of stock price volatility.